Exile : a conversation with N.T. Wright - Scott, James M., 1955- (Downers Grove : InterVarsity Press, 2017)
"N . T. Wright is well known for his view that the majority of Second Temple Jews saw themselves as living within an ongoing exile. This book engages a lively conversation with this idea, beginning with a lengthy thesis from Wright, responses from eleven New Testament scholars, and a concluding essay from Wright responding to his interlocutors"
Includes index.
Description based on print version record and CIP data provided by publisher
Keywords: Wright, N. T. -- Philosophy; Bible -- Criticism, interpretation, etc; Jews -- History -- 586 B.C.-70 A.D.; Exile (Punishment) -- Biblical teaching